Solid Propellant Motor Design: Comparison of Theoretical and Experimental Data - Gunsalam, Henry; Mohd. Yusof, Illyia (2006)
The objective of this paper is to compare the results of a solid rocket motor’s performance between theoretical calculations with empirical data collected from a static thrust bench in Propellant Laboratory, School of Aerospace Engineering, University Science of Malaysia. In this experiment, a simple and cheap solid propellant is manufactured, which consists of chemical compounds of potassium nitrate (KNO3), sulfur (S) and sugar (C12H22O11). Lesson learnt from this experiment will allow further research on the rocket’s flight trajectory prediction model being formulated for the completion of the dissertation